BIOLOGICAL ASPECTS, DENSITY AND DISTRIBUTION OF THE ALFONSINO (Beryx splendens) lN THE INDIAN OCEAN EKSLUSIVE ECONOMIC ZONE OF INDONESIA - Fayakun Satria; John Haluan; Eko Sri Wiyono; Wudianto Wudianto (Indonesian Fisheries Research Journal, 2008)
Deep water fisheries resources in the Indian Ocean ekslusive economic zone of Indonesia, has been investigated extensively in the year of 2004 to 2005. Recently a fishing operation of deep sea bottom trawl vessel F/B.